2022
DOI: 10.3847/2041-8213/ac9ebf
|View full text |Cite
|
Sign up to set email alerts
|

GOALS-JWST: Tracing AGN Feedback on the Star-forming Interstellar Medium in NGC 7469

Abstract: We present James Webb Space Telescope (JWST) Mid-Infrared Instrument (MIRI) integral-field spectroscopy of the nearby merging, luminous infrared galaxy, NGC 7469. This galaxy hosts a Seyfert type-1.5 nucleus, a highly ionized outflow, and a bright, circumnuclear star-forming ring, making it an ideal target to study active galactic nucleus (AGN) feedback in the local universe. We take advantage of the high spatial/spectral resolution of JWST/MIRI to isolate the star-forming regions surrounding the central activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 63 publications
4
23
1
Order By: Relevance
“…For example, García-Bernete et al (2022) found differences in the relative strengths of different PAH features in AGN host galaxies and starforming galaxies at kiloparsec scales. However, Lai et al (2022) recently found relatively small variations in PAH size and ionization and a decrease in PAH emission only in the direct line of sight of the AGN, using JWST observations. Similarly, Viaene et al (2020) found that the influence of the AGN is only relevant close to the nucleus.…”
Section: Qualitative Descriptionmentioning
confidence: 99%
“…For example, García-Bernete et al (2022) found differences in the relative strengths of different PAH features in AGN host galaxies and starforming galaxies at kiloparsec scales. However, Lai et al (2022) recently found relatively small variations in PAH size and ionization and a decrease in PAH emission only in the direct line of sight of the AGN, using JWST observations. Similarly, Viaene et al (2020) found that the influence of the AGN is only relevant close to the nucleus.…”
Section: Qualitative Descriptionmentioning
confidence: 99%
“…We consider mid-IR emission from the four MIRI bands imaged by PHANGS-JWST, F770W (7.7μm), F1000W (10μm), F1130W (11.3μm), and F2100W (21μm). To first order, the F770W and F1130W bands are expected to be dominated by emission from strong PAH bands while the F2100W filter covers mainly continuum emission from dust (e.g., see spectra in Draine & Li 2007;Smith et al 2007;Galliano et al 2018;Hensley & Draine 2022;Lai & Armus 2022). As discussed in Section 4.4, the situation with F1000W appears more ambiguous.…”
Section: Mid-infrared Bands and Band Ratiosmentioning
confidence: 99%
“…To do that, we reproject these masks to the JWST images. Since two of our galaxies contain an AGN, which produces hard ionizing radiation that can significantly affect the PAH fraction (e.g., Jensen et al 2017;García-Bernete et al 2022;Lai et al 2022), we exclude the centers of the galaxies from our analysis. Masks that isolate these particular environments are taken from Querejeta et al (2021).…”
Section: Selection Of the Nebulae And Associated Pah Emissionmentioning
confidence: 99%